Curcumin inhibits luteal cell steroidogenesis by suppression of extracellular signal regulated kinase - Endang Purwaningsih; Sri Kadarsih Soejono; Djaswadi Dasuki; Edy Meiyanto (Faculty of Medicine, Universitas Trisakti, 2012)
BackgroundCurcumin inhibits steroidogenesis in luteal cell cultures by inhibiting progesterone secretion. The site of action of curcumin on steroidogenesis in luteal cell cultures is as yet unkown. The purpose of this study was to determine the influence of curcumin on phosphorylation of extracellular signal regulated kinase (ERK) in steroidogenesis of luteal cell cultures. Methods An experimental study with control was conducted to investigate the site of action of curcumin by measurement of ERK phosphorylation in luteal cell cultures (LCC) after administration of luteinizing hormone (LH) and/or prostaglandin F2 alpha (PGF2á). The subjects of this study were luteal cell cultures derived from the corpus luteum of Sprague Dawley rat with superovulation induced by pregnant mare serum gonadotropin. The luteal cell cultures were devided into 16 groups, both with and without the addition of forskolin and each group contained 4 replicates samples. Curcumin was administered immediately following LH and/or PGF2á stimulation with or without addition of forskolin. The cell culture was then incubated for 24 h. ERK phosphorylation was measured by immunohistochemistry. Data on ERK phosphorylation was analyzed using one-way Anova, followed by multiple comparison tests. ResultsLH significantly increased ERK phosphorylation, whereas PGF2á significantly reduced ERK phosphorylation. Forskolin significantly increased ERK phosphorylation to a similar degree as LH. Curcumin inhibited ERK phosphorylation in both LH and forskolin-stimulated luteal cell cultures. ConclusionCurcumin inhibits ERK phosphorylation in luteal cell cultures by suppressing signal transduction upstream of ERK.